Fuzzy Sets Method of Reliability Prediction and Its Application to a Turbocharger of Diesel Engines. (2nd December 2013) - Li, Yan-Feng; Huang, Hong-Zhong; Zhang, Hanliang; Xiao, Ning-Cong; Liu, Yu
Abstract : Diesel engine is a complex electromechanical system which must operate reliably in harsh working environments. Reliability analysis and prediction play an important role during the design and development of diesel engines. However, in the traditional reliability methods, the analytical result obtained from the conventional failure mode, effects, and criticality analysis (FMECA) is not sufficient, which not only increases the workload of designers in charge of reliability, but also prolongs the product delivery time. This paper performs an in-depth reliability analysis with an emphasis on predicting the lifetime of diesel engine's turbocharger, in which the failure mode and the information of criticality provided by FMECA are fully utilized to carry out the reliability predictions. Meanwhile, to ensure the reliability prediction quality, this paper takes into account the expert knowledge and provides a possibility-based prediction model, in which the fuzzy analytic hierarchy process and the fuzzy comprehensive evaluation are combined to assess the criticality of the FMECA.